2015
DOI: 10.1177/1545968315576577
|View full text |Cite
|
Sign up to set email alerts
|

Combining Multiple Types of Motor Rehabilitation Enhances Skilled Forelimb Use Following Experimental Traumatic Brain Injury in Rats

Abstract: Background Neuroplasticity and neurorehabilitation have been extensively studied in animal models of stroke to guide clinical rehabilitation of stroke patients. Similar studies focused on traumatic brain injury (TBI) are lacking. Objective The current study was designed to examine the effects of individual and combined rehabilitative approaches, previously shown to be beneficial following stroke, in an animal model of moderate/severe TBI, the controlled cortical impact (CCI). Methods Rats received a unilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 64 publications
(100 reference statements)
4
41
0
Order By: Relevance
“…CCI to the CMC resulted in major impairments in both groups, as assessed at day 3. Similar to our recently published findings, 15 the combination RT regimen that included daily tray reaching, exercise, and forelimb constraint significantly improved forelimb function on the SPR task, compared to untrained controls, after CMC focused CCIs. There was a significant Group·Day interaction effect (F (7,168) = 9.72; p < 0.0001).…”
Section: Single-pellet Reaching Tasksupporting
confidence: 90%
See 4 more Smart Citations
“…CCI to the CMC resulted in major impairments in both groups, as assessed at day 3. Similar to our recently published findings, 15 the combination RT regimen that included daily tray reaching, exercise, and forelimb constraint significantly improved forelimb function on the SPR task, compared to untrained controls, after CMC focused CCIs. There was a significant Group·Day interaction effect (F (7,168) = 9.72; p < 0.0001).…”
Section: Single-pellet Reaching Tasksupporting
confidence: 90%
“…Two of our recent studies indicate that this assumption is flawed. 14,15 After a unilateral controlled cortical impact (CCI) over the caudal motor cortex (CMC) in rats, there are long-term forelimb impairments, similar to what is found following other models of damage to the motor cortex; however, we found that neural remodeling was severely blunted post-CCI compared to similarly placed and sized ischemic lesions.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations